2018
DOI: 10.1021/acs.macromol.7b02739
|View full text |Cite
|
Sign up to set email alerts
|

Vertically Oriented Nanostructures of Poly(3-dodecylthiophene)-Containing Rod–Coil Block Copolymers

Abstract: We synthesized star-shaped 18-arm polystyrene-block-poly(3dodecylthiophene) copolymers ((PS-b-P3DDT) 18 ) having lamellar microdomains, based on the cyclodextrin (CD) core. Without any surface modifications on a silicon substrate, thin films of (PS-b-P3DDT) 18 showed vertically oriented lamellar microdomains by thermal annealing. This is attributed to the entropic penalty induced by star-shaped chain architecture. In contrast, a parallel orientation was observed in the film morphology of the corresponding line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…In this case, however, perpendicular lamellae and cylinders were only observed in film thicknesses below 2L 0 and 3L 0 , respectively (this brings up an alluring question: would the thickness window for perpendicular features be expanded if the inner block were to have a lower γ than the outer block, analogous to a star‐shaped version of an ABA triBCP?). Similar results were produced with rod–coil star BCPs with 18 polystyrene‐ block ‐poly(3‐dodecylthiophene) (PS‐ b ‐P3DDT) arms . Although P3DDT had a significantly lower γ than PS, perpendicular microdomains were observed for film thicknesses below 2L 0 .…”
Section: Architecture Effectsupporting
confidence: 70%
See 1 more Smart Citation
“…In this case, however, perpendicular lamellae and cylinders were only observed in film thicknesses below 2L 0 and 3L 0 , respectively (this brings up an alluring question: would the thickness window for perpendicular features be expanded if the inner block were to have a lower γ than the outer block, analogous to a star‐shaped version of an ABA triBCP?). Similar results were produced with rod–coil star BCPs with 18 polystyrene‐ block ‐poly(3‐dodecylthiophene) (PS‐ b ‐P3DDT) arms . Although P3DDT had a significantly lower γ than PS, perpendicular microdomains were observed for film thicknesses below 2L 0 .…”
Section: Architecture Effectsupporting
confidence: 70%
“…Of these reports, reports that promote perpendicular microdomains via thermal annealing are highly promising because they are easily reproducible and industry friendly. These methods include substrate modification, use of top coats, incorporation of additives, exploitation of the architecture effect, use of modified or newly synthesized BCPs, and use of cold zone annealing techniques . Recently, the introduction of top coats has paved exciting roads to thermally induced perpendicular Si‐containing microdomains that could only be attained via solvent vapor annealing in the past.…”
Section: Introductionmentioning
confidence: 99%
“…However, rigid rods are not a perfect analogy for this behavior, because they are known to interdigitate rather than pack end−end, which would result in half the observed periodicity. 61 In order to pack end−end, there must be some rearrangement in the side chains in order to maintain a uniform interfacial area per junction between the two components in the lamellar morphology. In this molecule, the radius of the PS side chains is greater than that of the PLA side chains, and in the bulk, this differential between the side chain volumes can be remedied by changes in the backbone conformation.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that as the BBCP is increasingly confined, l p increases, up until the point where the entire chain is extended like a rigid rod. However, rigid rods are not a perfect analogy for this behavior, because they are known to interdigitate rather than pack end–end, which would result in half the observed periodicity . In order to pack end–end, there must be some rearrangement in the side chains in order to maintain a uniform interfacial area per junction between the two components in the lamellar morphology.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the thin-film morphology of star-shaped BCPs exhibited a different behavior from linear BCPs. Some research groups reported that vertically oriented cylindrical and lamellar microdomains of star-shaped BCPs were formed without pre- or post-treatment. , Kim and co-workers showed that cylindrical and lamellar microdomains of [(PMMA- b -PS) 18 ] were vertically oriented on diverse substrates . Also, Ho and co-workers reported that the vertical orientation of lamellae of three- and four-arm star-shaped PS -b -poly­(dimethylsiloxane) [(PS- b -PDMS) n ( n = 3, 4)] were formed by controlling the surface tension of the top film side by oxygen plasma treatment .…”
Section: Introductionmentioning
confidence: 99%